Human haematopoietic stem cells remember inflammatory stress - Andy G. X. Zeng; Murtaza S. Nagree; Niels Asger Jakobsen; Sayyam Shah; Angelica Varesi; Jasmine Ryu Won Kang; Alex Murison; Jin-Gyu Cheong; Sven Turkalj; Xuan Zhang; Felix A. Radtke; Tsega-Ab Abera; et al. (Nature, 2026)
Abstract Inflammation activates blood cells, contributing to ageing and malignancy 1–3 . Haematopoietic stem cells (HSCs) survive a lifetime of infection to sustain life-long haematopoiesis 1–9 , but how human HSCs respond and adapt to inflammatory stress is largely unknown. Here, to empirically understand this adaptation, we developed xenograft inflammation–recovery models and performed single-cell multiomics on xenografted human HSCs. Two transcriptionally and epigenetically distinct HSC subsets were identified with one, termed HSC inflammatory memory (HSC-iM), retaining a molecular memory of previous inflammatory treatments. The HSC-iM subset exhibited quiescence and restrained haematopoietic output. Molecularly, the HSC-iM program was enriched in HSCs from adult and paediatric samples across conditions ranging from COVID-19 recovery, sickle cell disease, ageing and clonal haematopoiesis, establishing both the validity of our xenograft models and the physiological relevance of HSC-iM. Clonal haematopoiesis mutations in HSC-iM attenuated the effects of inflammatory stress by promoting HSC activation and differentiation. Moreover, transmission of the pro-inflammatory HSC-iM transcriptional program to differentiated immune progeny was demonstrated in xenograft and physiological settings. Finally, HSC-iM program enrichment in circulating blood cells was associated with a heightened risk score for all-cause mortality in population cohort analyses, underscoring the clinical relevance of this newly identified HSC subset in characterizing heterogeneous health outcomes across a lifetime.